Retired College Student Athletes' Psychological Well-Being: A Prospective Analysis. - Shander, Karolina; Petrie, Trent; Moore, E. Whitney G. (Journal of Loss & Trauma, 2024)
For college student athletes, graduation coincides with a loss of competitive careers and athletic identities and begin a potentially traumatic transition to a new life phase. However, how athletes' experience this developmental transition may be influenced by their readiness to retire. Thus, we prospectively examined how NCAA student athletes' (N = 166) psychological well-being changed from graduation/retirement (T1) to four months later (T2) and determined the extent their readiness to retire, as represented by 12 key psychosocial dimensions (e.g., social support, athletic identity) predicted well-being at T2. Athletes completed a 12-item measure of retirement readiness at T1, measures of depressive symptomatology, body satisfaction, and life satisfaction at T1 and T2. Through regressions analyses, and controlling for gender and T1 well-being scores, we found that athletes who developed a new life focus and had positive social support systems at retirement from sport were more satisfied with their lives and less depressed four to five months later. For the athletes' T2 body satisfaction, only their T1 satisfaction was a significant predictor. As one of the first studies to longitudinally examine collegiate athletes' well-being over the first six months of retirement, our findings provide direction for additional research and development of programming that focuses on helping athletes maintain and extend their support networks as they transition from their teams and develop a new purpose and direction in their lives as they lose what had been present for them through their sport involvement. Implications for assisting collegiate athletes in transition from sport are provided.